The Future European Natural Gas Market - are lower gas prices attainable? - Eirik Lund Sagen; Finn Roar Aune (Statistics Norway, Research Department, 2004)
We analyse effects of various natural gas supply scenarios in a liberalised Western European energy market in 2010. Our starting point is the uncertainties about future natural gas exports from Russia and LNG-producing countries. Our results indicate that the average natural gas producer price in Western Europe is likely to be higher in 2010 than the average historical price the last 15 years, even in an optimistic supply scenario. We find only modest effects on both average natural gas producer prices and trade patterns of radical changes in supply volumes. However, there are significant country specific differences, primarily related to the reliance on Russian gas exports and the use of gas fired power generation
Keywords: D58; F17; Q31; Q41; 330; Electricity; energy modeling; natural gas; liberalized energy markets; LNG; Russia